GENDER DIFFERENCE OF KNOWLEDGE, PRACTICES TOWARDS HANDS WASHING AND MASKS WEARING DURING COVID‐19 PANDEMIC IN THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Purposes: This study aimed to compare knowledge and practices of male and female towards hands washing and masks wearing during COVID‐19 (coronavirus disease 2019) pandemic in Thong Nhat hospitalMaterials   and   method: We conducted a cross-sectional study among patients who come to outpatient care at Thong Nhat Hospital, Ho Chi Minh City from May 2020 to July 2020. Researchers interviewed patients directly using prepared questionnaires.Results: A total of 1,555 patients were included into the study with 804 males (51.7%)  and 751 females (48.3%). There were significantly different between the male and female groups about age, qualification and employment status (p
Keywords: COVID-19; knowledge; practices; gender.